A Critical Approach to Climate Change Adaptation Discourses, Policies, and Practices - Klepp, Silja; Chavez-Rodriguez, Libertad (Taylor & Francis, 2018)
This edited volume brings together critical research on climate change adaptation discourses, policies, and practices from a multi-disciplinary perspective. Drawing on examples from countries including Colombia, Mexico, Canada, Germany, Russia, Tanzania, Indonesia, and the Pacific Islands, the chapters describe how adaptation measures are interpreted, transformed, and implemented at grassroots level and how these measures are changing or interfering with power relations, legal pluralismm and local (ecological) knowledge. As a whole, the book challenges established perspectives of climate change adaptation by taking into account issues of cultural diversity, environmental justicem and human rights, as well as feminist or intersectional approaches. This innovative approach allows for analyses of the new configurations of knowledge and power that are evolving in the name of climate change adaptation. This volume will be of great interest to students and scholars of climate change, environmental law and policy, and environmental sociology, and to policymakers and practitioners working in the field of climate change adaptation.